Isolation of 12 Bacterial endophytes from some mangrove plants and determination of, antimicrobial properties of the isolates and the plant extracts - Ibrahim M.S Eldeen (International Journal of Phytomedicine, 2014)
The mangrove designates a highly productive ecosystem with important economic and environmental functions. Endophytes are microorganisms that live in the intercellular spaces of plant tissue. This study aimed to isolate and identify bacterial endophytes from five mangrove plants and to determine, antimicrobial properties of the isolates and the plant extracts against four pathogenic bacteria: Bacillus cereus, Staphylococcus aureus, Escherichia coli and Salmonella typhimurium using the deferred antagonism and the microdilution assays. Of the total 33 endophytic bacteria isolated, 18 strains showed antagonistic effects. Twelve of these inhibitors were identified using VITEK 2. Crude protein from each of the producer strains were precipitated and tested for minimum inhibitory concentration (MIC) against the pathogenic bacteria using the microdilution assay. Best activities were recorded for Staphylococcus intermedius and Bacillus licheniformis (19 µl/ml) against B. cereus. The S. intermedius also inhibited growth of both S. aureus and S. typhimurium (39 µl/ml). Staphylococcus lentus, Bacillus pumilus and Bacillus coagulans possessed activities against S.typhimurium with an MIC value of 78 µg/ml. For the plant extract, the lowest MIC value (9.7 µg/ml) was obtained by Aviecenna lanata and Sonneratia caseolaris against B.cereus. S.caseolaris also showed significant inhibitory effects against E.coli and S.typhimurium (19.5 µg/ml). Our results indicated the potentiality of the isolated bacterial endophytes as a producer of antimicrobial substances which could be developed for various applications. MIC values obtained for the plant extracts in this study showed the effective plant part and extracts to be further developed and profiled as antimicrobial agents.